The Hungarian eco-innovational performance in Europe - Gáspár Gergely (Taylor : gazdálkodás- és szervezéstudományi folyóirat, 2015)
After the end of the late ’90s, when the innovational processes was tending to be a more and more important part of the economy, the new millennium brought a real boom in this section. These innovational processes became one of the main drivers of the economy, especially in the corporate sector. In these decades, a new challenge appeared and widened on the market: the implementation of the sustainable, environmental a social friendly management. A few years after the financial crisis, some experts claim, that the innovative ecological developments could be one of the best chances to increase the performance of the enterprises – in the SME sector also – and of the national and international markets too. In this situation, when the EU plans to support eco-innovation as one of the main topics of the new financial period, it is excessively interesting, how Hungary can turn these opportunities for benefits – based on a very unique-structured, but not so independent local market.